Frequency of Herpes Simplex Encephalitis in Children of a Tertiary Care Hospital: a cross-sectional study - Zahid, Nimra; Sher, Atika; Hussain, Mehtab (Infectious Diseases Journal of Pakistan, 2022)
Introduction: Herpes Simplex encephalitis is a life-threatening condition. The burden of Herpes Simplex Encephalitis in children is not known in Pakistan. So, this study was conducted to determine the frequency of Herpes Simplex Encephalitis in children presenting with clinical encephalitis to a tertiary care hospital. Methods: This cross-sectional study was conducted in the Department of Paediatrics, Liaquat National Hospital, Karachi from 7th April 2018 to 6th October 2018. A total of 149 consecutive patients of age between 1 month to 12 years, either gender presenting with signs or symptoms of encephalitis (clinical assessment) were included in this study. Patients with encephalopathy secondary to sepsis, metabolic causes, or space-occupying lesions were excluded from this study. After taking informed consent, a lumbar puncture was done by a trained senior resident and cerebrospinal fluid was sent for detailed report, culture, and herpes simplex polymerase chain reaction. Data were recorded on preapproved proforma and analyzed using SPSS. Results: Mean age was 4.30±3.11 years. Overall, 59.7% of the patients were male and 40.3% were female. In the cerebrospinal fluid detailed report, the mean white blood cells, red blood cells, glucose, and proteins were 86.63±344.69 /cm3, 2283.62±17342.38 /cmm, 90.61±33.3 mg/dL, and 66.49±112.02 g/dl respectively. In this study, 30.9% of children were malnourished. The frequency of Herpes Simplex Encephalitis was 29 (19.5%). Stratified analysis by gender, age, and malnutrition was not found to be effect modifiers. Conclusion: Results showed 19.5% HSV-PCR positive cases among encephalitis children. Gender, age, and malnutrition were not found to be effect modifiers. Keywords: Frequency, Herpes simplex, Encephalitis, Polymerase chain reaction